2018
DOI: 10.1080/10903127.2017.1413465
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory Use of the Backboard is Associated with Increased Frequency of Thoracolumbar Imaging

Abstract: A shift from a spinal immobilization protocol to a spinal motion restriction protocol was associated with a decrease in backboard utilization by EMS providers and a decrease in thoracolumbar spine imaging by ED providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As previous studies have suggested, patients on an LSB for periods of time report increased pain, tissue breakdown, and respiratory compromise, which led to "false-positive exams for midline vertebral tenderness", 9 and therefore, increased imaging and cost of care. 4,8,12 Clemency et al 12 in 2018 observed that patient charts before and after the implementation of the new SMR protocol demonstrated the decrease in backboard utilization was associated with a decrease in spine imaging in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have suggested, patients on an LSB for periods of time report increased pain, tissue breakdown, and respiratory compromise, which led to "false-positive exams for midline vertebral tenderness", 9 and therefore, increased imaging and cost of care. 4,8,12 Clemency et al 12 in 2018 observed that patient charts before and after the implementation of the new SMR protocol demonstrated the decrease in backboard utilization was associated with a decrease in spine imaging in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Joining these providers in RSEs are those that have long transport times that can attest to the countless patients that were made worse after emesis (that later developed aspiration pneumonia), or their myofascial strain that was compounded by the limited ability to move for extended periods. 34,35 Members of WADEM called for a round-table discussion at the biannual WADEM Congress in Toronto in May 2017 to discuss the continued lack of acceptance of science in RREs hindering the triage and treatment of patients injured in a RSE with potential spinal injuries. 27 A author of this study (JC) lead this round table discussion, with over 50 interested participants from all professional levels of training and experiences from the full breadth of RSEs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications challenge the ubiquitous application of cervical collars or the use of spinal boards in the extrication and transportation phase following an MVC [87][88][89][90]. These papers, based on expert opinion and an analysis of 'excess imaging' associated with immobilisation suggest alternative approaches including gentle patient handling techniques and selfextrication [87][88][89][90].…”
Section: Immobilisationmentioning
confidence: 99%